Hubungan Kemampuan Memahami Cerpen dengan Kemampuan Menulis Naskah Drama Siswa Kelas VIII SMPN 9 Sijunjung - Efendi, Novita; Thahar, Harris Effendi; Tamsin, Andria Catri (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2013)
The aim of this research is to describe the relationship between the ability in comprehending the short story and the ability in writing the drama manuscript for the VIII gradeâ€™s student at , junior high school, nine, Sijunjung. The type of this research is quantitative research using descriptive and the statistic correlation methods. Population and sample in this research is the student of the VIII grade at junior high school ,nine, Sijunjung. The population in this research is 34 students who are registered in academic year of 2012/2013. This population involves two class which the population is sample because the population is less than 100 students.Â  The result of research shows that the ability of student in comprehending the short story highly assists them in writing the drama manuscript. Furthermore, using the statistic correlation method, it shows that relationship between the student ability in understanding the short story and the student ability in writing the drama manuscript is significant on the degree of freedom, n-2, and it is significant at 95 % of confident level since 6.41 of t-statistic value is greater than 1.70 of t-table value.